Tantangan Mengkomunikasikan Informasi Beasiswa: Studi Kasus di Negara Berkembang Suriname - Kartoredjo, Ruiz Levay Jonothan; Hasfi, Nurul (PRoMEDIA, 2023)
AbstractCommunication is not just about the process of transmitting information, but also requires a well-crafted strategy. Communication strategies are built on a foundation of clear objectives, thoughtful planning, and an understanding of how different communication channels can be used to achieve specific goals. Not having any communication strategy could lead to many issues. This research is done in Suriname because of its education challenges, specifically in communicating scholarship information to the public. A qualitative case study is conducted using in-depth interviews, qualitative data analysis approach and 11 purposive informants to investigate how scholarship information is communicated at the Bureau Education Information and Study Facilities (BOS) in Suriname. This study applied the theory of the Montreal School Approach to Communicative Constitution of Organizations that will explain how organizations are formed and represented through ongoing interactions based on five phases of translations. The study found that BOS is responsible for disseminating information about international scholarships and is reliable in the process but lacks extensive communication policies. However, students in Suriname face challenges due to poor communication of scholarship information. Based on the findings, this study includes suggestions such as the need for creating engaging content to communicate scholarship information and utilizing other communication channels to reach a wider audience.Keywords: Scholarship, Information, Communication process, Communication strategy, Montreal School ApproachAbstraksi Komunikasi bukan hanya berbicara tentang proses penyampaian informasi, tetapi juga bagaimana strategi komunikasi tersusun dengan baik. Strategi komunikasi idealnya dibangun di atas fondasi tujuan yang jelas, perencanaan yang matang, dan pemahaman tentang saluran komunikasi tepat sehingga bisa mencapai tujuan tertentu. Tidak adanya strategi komunikasi dapat menimbulkan banyak masalah. Penelitian ini menggunakan konteks negara berkembang Suriname yang saat ini memiliki tantangan dalam dunia pendidikan, khususnya dalam mengkomunikasikan informasi beasiswa kepada publiknya. Wawancara mendalam terhadap 11 informan yang dipilih secara purposif dilakukan untuk mengidentifikasi bagaimana informasi tentang beasiswa dikomunikasikan Biro Informasi Pendidikan dan Fasilitas Belajar (BOS) di Suriname. Teori Montreal School Approach to Communicative Constitution of Organizations diterapkan untuk menjelaskan bagaimana komunikasi dilakukan oleh organisasi dalam lima langkah strategi. Studi ini menemukan bahwa BOS bertanggung jawab untuk menyebarkan informasi mengenai beasiswa internasional dan dapat diandalkan dalam prosesnya. Namun demikian, proses ini belum bisa terlaksana dengan maksimal. Mahasiswa Suriname menghadapi tantangan berupa buruknya komunikasi informasi beasiswa karena tidak semua fase strategi komunikasi terlaksana dengan baik. Berdasarkan data, studi ini juga menyarankan perlunya ada konten yang komprehensif dengan memanfaatkan saluran komunikasi yang mudah diakses dan mampu menjangkau audiens yang lebih luas.Kata Kunci: Beasiswa, Informasi, Proses Komunikasi, Strategi Komunikasi, Pendekatan Sekolah Montreal